Management and Outcomes of Acute Respiratory Distress Syndrome Caused by Blastomycosis: A Retrospective Case Series. Issue 18 (May 2016) - Schwartz, Ilan S.; Embil, John M.; Sharma, Atul; Goulet, Stephen; Light, R. Bruce
Abstract : Abstract: Acute respiratory distress syndrome (ARDS) is an uncommon, highly fatal, and poorly understood manifestation of blastomycosis. Optimal management remains unknown, including the roles of adjunctive corticosteroids and extracorporeal membrane oxygenation (ECMO). We conducted a retrospective chart review of patients with ARDS caused by blastomycosis, managed in intensive care units in Manitoba, Canada, from 1992 to 2014. ARDS was defined using the Berlin definition. Corticosteroid therapy was defined as ≥150 mg cortisol equivalent in 24 hours. Logistic regression was used to identify determinants of a fatal outcome, and bootstrap resampling was used to assess sample size requirements. Forty-three patients with ARDS caused by blastomycosis were identified. ARDS was mild, moderate, and severe in 2 (5%), 12 (28%), and 29 (67%) patients, respectively. Management included amphotericin B (n = 42, 98%), vasopressors (n = 36, 84%), corticosteroids (n = 22, 51%), renal replacement (n = 13, 30%), and ECMO (n = 4, 11%). Seventeen patients (40%) died. All patients treated with ECMO survived ( P  = 0.14). Corticosteroids were not associated with survival benefit in univariate ( P  = 0.43) or multivariate analyses (odds ratio 0.52, 95% confidence interval 0.11–2.34). Bootstrap studies indicated that almost 500 patients would be needed to confirm a significant reduction in mortality from corticosteroids (type I error = 0.05, power = 80%). Blastomycosis is an uncommon, albeit important, cause of ARDS in this geographic area. Given the rarity of disease and the large cohort needed to demonstrate mortality benefit, the role of adjunctive therapies, including corticosteroids and ECMO, may remain unconfirmed, and clinical judgment should guide management decisions. Abstract : Supplemental Digital Content is available in the text